Self-organization and Self-development as Key Factors in Improving Productivity - GAISINA, Lyutsiya Mugtabarovna; BELONOZHKO, Marina Lvovna; KIRICHUK, Stepan Mikhailovich; SULTANOVA, Ekaterina Alexandrovna; TUMANOVA, Aleksandrina Yurievna (Journal of Advanced Research in Law and Economics; Vol 8 No 2 (2017): Volume VII, Issue 2(24), Spring 2017, 2017)
In the oil and gas industry enterprises dominate the complex multi-level hierarchical organizational structures that in view of the objective social features create a lot of obstacles in the implementation of administrative interactions; employees of such organizations do not become part of the organizational spaces, do not become the subject of a control system, which leads to the loss of human capacity and unrealized potential ‘human resources.’ Socially-oriented methods of management labor collectives, such as a creation of the comfortable psychological climate, the formation of the united creative team, the support of the staff by the management, at the industry enterprises are used, but there is no comprehensive and holistic method of an implementation, it is not taken into account the sectoral specificity and nature of work, ignored the departments and units during the impact, all this reduces the efficiency and effectiveness of methods. There was a gap of social relations system in the enterprise, the majority of employees are focused on the temporary nature of work (the theme - ‘save money’ rather than develop professionally on the basis of the enterprise), a low motivation for the continuation of career, which significantly increases the instability of the industry during the crisis. In this article the results of sociological research, confirming the problems which are mentioned above. The index dissociation opinions of employees and managers are designed and the index of their consensus estimates too. The conclusions about the need to review the relationship of the individual to work and in the human resources management framework is essential to put the incentives for the self-development as a key factor in improving productivity, combined with a high level of the self-organization and labor discipline.